2017
DOI: 10.14474/ptrs.2017.6.3.113
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Schroth’s three-dimensional exercises in combination with respiratory muscle exercise on Cobb’s angle and pulmonary function in patients with idiopathic scoliosis

Abstract: Objective: The objective of this study was to investigate the effects of Schroth's three-dimensional exercises in combination with respiratory muscle exercise (SERME) on Cobb's angle and functional movement screen (FMS). Design: Randomized controlled trial. Methods: Fifteen subjects with scoliosis were randomly assigned to two groups. Eight subjects were assigned to the experimental group and seven subjects were assigned to the control group. The experimental group underwent SERME using SpiroTiger (Idiag, Swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 13 publications
1
27
0
3
Order By: Relevance
“…Although the method used varies, all techniques adhere to the same principle, namely: 1) three-dimensional self-correction; 2) training activities of daily living; and 3) stabilization of corrected postures [34]. Updated studies have reported promising effects of SSE on curve regression [35][36][37][38][39][40][41][42][43][44][45][46][47][48], which warrants a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the method used varies, all techniques adhere to the same principle, namely: 1) three-dimensional self-correction; 2) training activities of daily living; and 3) stabilization of corrected postures [34]. Updated studies have reported promising effects of SSE on curve regression [35][36][37][38][39][40][41][42][43][44][45][46][47][48], which warrants a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The previous systematic reviews (33,52), analyzed the same ve studies (35,37,41,45,48) included in our review, revealed a signi cant heterogeneity by statistical testing and concluded that no pooled effect sizes could be reliably reported. In addition, our review included ve more updated clinical trials that showed notable methodological heterogeneity: one CCT was conducted with a large sample size (n=99) but no comparative untreated controls (40); four studies, including one CCT (38) and three RCTs (36,46,47), were conducted with small sample sizes (n<50) which could mask variations and build up of systematic errors. Moreover, those four studies (36,38,46,47) in which all included bracing strategy, this introduced confounding effects of bracing and SSE in treating AIS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our review included ve more updated clinical trials that showed notable methodological heterogeneity: one CCT was conducted with a large sample size (n=99) but no comparative untreated controls (40); four studies, including one CCT (38) and three RCTs (36,46,47), were conducted with small sample sizes (n<50) which could mask variations and build up of systematic errors. Moreover, those four studies (36,38,46,47) in which all included bracing strategy, this introduced confounding effects of bracing and SSE in treating AIS. Therefore, considering the notable heterogeneity of enrolled studies, a meta-analysis was not performed in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process was repeated at least three times. The highest value was selected as the FVC and FEV1 [20].…”
Section: Pulmonary Functionmentioning
confidence: 99%